2008
DOI: 10.21273/hortsci.43.3.685
|View full text |Cite
|
Sign up to set email alerts
|

Iron Induces Root and Leaf Ferric Chelate Reduction Activity in Grapevine Rootstock 140 Ruggeri

Abstract: Ferric chelate reduction (FCR) activity of roots and leaves was determined in the grapevine rootstock 140 Ruggeri under iron (Fe)-deficient and Fe-sufficient conditions. Micropropagated plants were subjected to 0 or 40 μm Fe(III) EDTA in hydroponic culture. After 10 days of treatments, Fe-deficient plants had a lower level of root FCR activity and chlorophyll content compared with Fe-sufficient plants. Iron supply (20 μm) to Fe-deficient plants caused a rapid incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…Furthermore, the literature reports of hydroponics-grown Fe-deficient (1 μM) and Fe-sufficient (20 μM) 140R cuttings displaying enhanced FCR activity under the former conditions 26 . The fact that our results agree with those reported by Siminis et al 27 , who used similar plant material (micropropagated 140R) and grew the plants in the absence of Fe (0 μM), stresses the importance of the presence of at least some Fe for the FCR enzyme to function 33 . Significant differences in the levels of FCR activity emerged between Fe-replete Ramsey and 140R, with the latter variety displaying the higher value (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the literature reports of hydroponics-grown Fe-deficient (1 μM) and Fe-sufficient (20 μM) 140R cuttings displaying enhanced FCR activity under the former conditions 26 . The fact that our results agree with those reported by Siminis et al 27 , who used similar plant material (micropropagated 140R) and grew the plants in the absence of Fe (0 μM), stresses the importance of the presence of at least some Fe for the FCR enzyme to function 33 . Significant differences in the levels of FCR activity emerged between Fe-replete Ramsey and 140R, with the latter variety displaying the higher value (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were also obtained by Venturas et al (2014) that reported lower FCR activity in chlorotic elm species compared to plants that developed in Fe sufficient conditions. Similar behaviour has reported in grapevine and in tomato (Siminis and Stavrakakis, 2008;Zouari et al, 2001). To rationalize the results we hypothesize that the root FCR activity of the cultivar "Diamante" seems to be regulated by Fe itself.…”
Section: Discussionsupporting
confidence: 84%
“…Little is known about the specific mechanisms used by grape rootstocks to absorb nutrients. Nikolaou et al (2003) and Smart et al (2005) point out that absorption is related to the increased density of root hairs as a response to the deficiency of a nutrient; or as Siminis and Stavrakakis (2008) report, absorption is related to the increased capacity of the roots to assimilate specific nutrients. In all cases, more study is required to understand the influence of the root system in mineral absorption (Nikolaou et al, 2000).…”
Section: Introductionmentioning
confidence: 99%